Content analysis of papers published in Malaysian Journal of Movement, Health and Exercise (MoHE) between 2013 and 2022 - Hashim, Roosfa (Wolters Kluwer - Medknow, 2023)
Background: there are several scientific journals in the field of sports science that have been published in Malaysia. One of these journals that has been published regularly is Malaysian Journal of Movement, Health and Exercise (MoHE). Aims and Objectives; The Purpose of this study was to analyse the development trends of subjects studied and published in MoHE between 2013 and 2022. Materials and methods: A total of 174 articles published in 18 issues of MoHE between 2013 and 2022 were analysed . This study was conducted quantitatively by tracking the highest percentage of various subfield that have been published in MoHE. Therefore, the focus of this study is on the keywords listed at the end of each abstract for articles that have been published in MoHE. Results: This study found that MoHE has become a popular platform of researchers in the field of sports science to publish their research findings. Several subjects and important subtopics in the field of sports science have been identified as the focus of papers published in the MoHE. Conclusion: This study has proven that MoHE has been accepted as a platform scientific debate and discussion in the field of sports science.